SISTEM INFORMASI LAYANAN KESEHATAN BERBASIS MOBILE YANG MENGINTEGRASIKAN INSTANSI LAYANAN KESEHATAN DI KOTA PEKALONGAN - Susanto, Eko Budi; Christianto, Paminto Agung; Kurniawan, M. Faizal (JURNAL LITBANG KOTA PEKALONGAN, 2016)
THE ABSENCE OF MOBILE-BASED HEALTH INFORMATION SYSTEMS THAT CAN INTEGRATE ALL HOSPITALS, HEALTH CENTERS, HEALTH CLINICS AND PHARMACIES IN PEKALONGAN, WILL BOTHER PEOPLE WHO NEED HEALTH INFORMATION QUICKLY, ACCURATELY, ANYTIME AND ANYWHERE. LIKE SCHEDULE DOCTOR, INPATIENT ROOM AVAILABILITY INFORMATION FOR ALL HEALTH INSTITUTIONS, SO WITH THIS INFORMATION SO PEOPLE CAN MAKE DECISIONS QUICKLY AND ACCURATELY.THIS STUDY INTENDS TO SUPPORT A SOLUTION TO THE DIFFICULTY IN OBTAINING ACCURATE INFORMATION, SUCH AS THE SCHEDULE OF DOCTORS, INPATIENT, THE STOCK OF BLOOD, HOSPITAL THROUGH THE DEVELOPMENT OF INFORMATION SYSTEMS THAT INTEGRATE HEALTH-CARE INSTITUTIONS IN THE CITY OF PEKALONGAN